Coping Strategies and Health-Related Quality of Life in Breast Cancer Survivors - Ana Agrelo-Fernández; Lucía Fernández-Arce; Ana Llaneza-Folgueras; Ana Isabel Encinas-Muñiz; María Olivo del Valle; Alberto Lana (European Journal of Investigation in Health, Psychology and Education, 2025)
Background: The aim was to explore the association between coping strategies (CSs) and health-related quality of life (HRQoL) in breast cancer (BC) survivors and to analyze the role of relevant sociodemographic and clinical variables. Methods: A cross-sectional study involving 305 women under follow-up for surgically treated BC in Spain. CSs were measured using the Brief Coping Orientation to Problems Experienced Scale and the HRQoL with the Short-Form Health Survey (SF-12). Results: The mean age at BC diagnosis for participants was 57.4 years, with 60.3% of diagnoses at the local stage. Most frequent complementary treatments were radiotherapy (53.4%) and chemotherapy (33.1%). Adaptative CS scores were positively associated both with higher physical HRQoL (adjusted regression coefficient: 2.19; 95% confidence interval: 0.11; 4.27, p-value: 0.039) and mental HRQoL scores (coef.: 2.65: 95%CI: 0.25; 5.04, p-value: 0.030). Maladaptive CS scores were inversely associated with mental HRQoL scores (coef.: −3.92; 95%CI: −6.62; −1.22, p-value: 0.005). The effects were stronger among women with a favorable BC prognosis. Conclusions: Adaptive CSs positively affected the physical and mental HRQoL, while maladaptive CSs negatively affected the mental HRQoL. Therefore, psychosocial interventions that promote adaptive CSs and avoid maladaptive ones could improve the well-being of women with a favorable BC prognosis.